2013
DOI: 10.1136/jclinpath-2012-201323
|View full text |Cite
|
Sign up to set email alerts
|

Downgrading of biopsy based Gleason score in prostatectomy specimens

Abstract: The frequency of GS 7 in biopsies subsequently downgraded in RP is low and is associated with International Society of Urological Pathology modified Gleason grade 4 patterns. Downgrading could be attributed in most cases to the presence of a tertiary Gleason grade 4 pattern in the RP specimen. Inter-observer agreement for the presence of tertiary grade 4 in RP specimens is moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Discrepancies mainly arise from the distinction of grade 3 from ill‐formed (Figure A–C) and small‐fused glands (Figure D). Downgrading a biopsy Gleason score 7 to a Gleason score 6 at prostatectomy could be attributed in most cases to these two patterns in the biopsy . The sizes of well‐defined Gleason grade 3 glands range from large‐size, difficult to separate from benign glands, to ever smaller‐sized glands, and there is no abrupt distinction from ill‐formed glands (Figure A).…”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancies mainly arise from the distinction of grade 3 from ill‐formed (Figure A–C) and small‐fused glands (Figure D). Downgrading a biopsy Gleason score 7 to a Gleason score 6 at prostatectomy could be attributed in most cases to these two patterns in the biopsy . The sizes of well‐defined Gleason grade 3 glands range from large‐size, difficult to separate from benign glands, to ever smaller‐sized glands, and there is no abrupt distinction from ill‐formed glands (Figure A).…”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
“…Downgrading a biopsy Gleason score 7 to a Gleason score 6 at prostatectomy could be attributed in most cases to these two patterns in the biopsy. 84 The sizes of well-defined Gleason grade 3 glands range from large-size, difficult to separate from benign glands, to ever smaller-sized glands, and there is no abrupt distinction from ill-formed glands ( Figure 5A). Based on an interobserver variation study, Zhou et al suggested that a minimum of 10 'ill-formed' glands constituting a separate tumour area in an otherwise Gleason grade 3 pattern tumour would be required to assign a grade 4 ( Figure 5B,C).…”
Section: Distinction Of Grade 3 Versus 4 Patternsmentioning
confidence: 99%
“…However, the Gleason score of the biopsy sample, which remains the most powerful prognostic marker, is inaccurate in a large percentage of patients especially when only a small volume tumor is sampled during biopsy. The vast majority of biopsies are scored as either Gleason 6 or 7 and yet up grading or down grading occurs in 14–51% and 9%, respectively when comparing the Gleason score of the biopsy to that found in the prostatectomy specimen . Likewise, clinical stage poorly estimates final pathological stage , an important predictor of clinical outcome, second only to Gleason score .…”
Section: Introductionmentioning
confidence: 99%
“… 2 3 Although an upgraded Gleason score after RP is most common, 7.4% to 30% of the Gleason score 7 (3 + 4) biopsies were shown to be downgraded to Gleason score 6 (3 + 3) or lower at RP. 17 In our study, when we compared the Gleason score between TRUSBX and RP, 11 (6%) cases were overestimated by TRUSBX. Freedland et al 18 described 123 (11%) downgrading cases (lower RP grade than biopsy grade) among 1113 men treated with RP.…”
Section: Discussionmentioning
confidence: 53%